Multiple nano-filaments based efficient resistive switching in TiO2 nanotubes array influenced by thermally induced self-doping and anatase to rutile phase transformation. (23rd December 2020) - Hazra, Arnab; Tripathi, Ashutosh; Jan, Atif; Kundu, Souvik; Boppidi, Pavan Kumar Reddy
Abstract: In this paper, the impact of thermally induced self-doping and phase transformation in TiO2 based resistive random-access memory (ReRAM) is discussed. Instead of a thin film, a vertically aligned one-dimensional TiO2 nanotube array (TNTA) was used as a switching element. Anodic oxidation method was employed to synthesize TNTA, which was thermally treated in the air at 350 °C followed by further annealing from 350 °C to 650 °C in argon. Au/TiO2 nanotube/Ti resistive switching devices were fabricated with porous gold (Au) top electrode. The x-ray diffraction results along with Raman spectra evidently demonstrate a change in phase of crystallinity from anatase to rutile, whereas photoluminescence spectra revealed the self-doping level in terms of oxygen vacancies (OV) and Ti interstitials (Tii ) as the temperature of thermal treatment gets increased. The electrical characterizations establish the bipolar and electroforming free resistive switching in all the samples. Among those, the ReRAM sample S3 thermally treated at 550 °C displayed the most effective resistive switching properties with R OFF / R ON of 10 2 at a read voltage of −0.6 V and a SET voltage of −2.0 V. Moreover, the S3 sample showed excellent retention performance for over 10 6 s, where stable R OFF / R ON  ≈ 107 was maintained throughout the experiment.